Wear Behavior Evaluation In Simulated Body Fluid of A Modified Ti-6Ai-4V Alloy by DC Glow Plasma Nitriding - Safa Hussain Ali; Thair L (Global Scientific Publishing, 2024)
As implant materials in biomedical application titanium and titanium alloys are used frequently in this filed due to high strength to weight ratio, good corrosion resistance and good biocompatible when compared with other material used in biomedical application (such as stainless steel and cobalt base alloys). But this alloy when reacted with body fluid will release aluminum and vanadium then causes neurological disorders and toxicity in human system. ."The glow discharge is just one of many forms of gaseous discharges, often called plasma". An electric discharge can see it when two electrodes are inside to a pipe and linked to a power supply the pipe can be bellyful with different gasses or evacuated electrical current is go past between two special electrode. The plasma nitriding process was performed at different nitriding times (5, 10, and 15 h), and the effect of plasma nitriding was examined on the chemical compassion of Ti–6Al–4V alloy and the appearance of phases was studied by scanning electron microscopy, FESEM , X-ray diffraction (XRD) and pin on disk wear resistance. The results indicate that the formation of layers and phases Ti2N and Ti2N3−x on a surface of the alloy were achieved, which would improve the surface characteristics of wear resistance in simulated body fluid.
Keywords: characteristics; plasma; resistance; formation